Moss-pathogen interactions: a review of the current status and future opportunities - Zhang, Huan; Yang, Qilin; Wang, Leyi; Liu, Huawei; Zhang, Daoyuan; Duan, Cheng-Guo; Li, Xiaoshuang (Frontiers in Genetics, 2025)
In complex and diverse environments, plants face constant challenges from various pathogens, including fungi, bacteria, and viruses, which can severely impact their growth, development, and survival. Mosses, representing early divergent lineages of land plants, lack traditional vascular systems yet demonstrate remarkable adaptability across diverse habitats. While sharing the fundamental innate immune systems common to all land plants, mosses have evolved distinct chemical and physical defense mechanisms. Notably, they exhibit resistance to many pathogens that typically affect vascular plants. Their evolutionary significance, relatively simple morphology, and well-conserved defense mechanisms make mosses excellent model organisms for studying plant-pathogen interactions. This article reviews current research on moss-pathogen interactions, examining host-pathogen specificity, characterizing infection phenotypes and physiological responses, and comparing pathogen susceptibility and defense mechanisms between mosses and angiosperms. Through this analysis, we aim to deepen our understanding of plant immune system evolution and potentially inform innovative approaches to enhancing crop disease resistance.